At Westonci.ca, we connect you with the best answers from a community of experienced and knowledgeable individuals. Discover detailed answers to your questions from a wide network of experts on our comprehensive Q&A platform. Discover detailed answers to your questions from a wide network of experts on our comprehensive Q&A platform.
Sagot :
To solve the given system of equations:
[tex]\[ \begin{cases} x + y = 7xy \\ 2x - 3y + xy = 0 \end{cases} \][/tex]
we need to find the values of [tex]\( x \)[/tex] and [tex]\( y \)[/tex] that satisfy both equations.
### Step 1: Rearrange and simplify the equations
First, let's work with the first equation:
[tex]\[ x + y = 7xy \][/tex]
We can rearrange this to express it in a different form:
[tex]\[ x + y - 7xy = 0 \][/tex]
Next, let's look at the second equation:
[tex]\[ 2x - 3y + xy = 0 \][/tex]
### Step 2: Solve one equation for one variable
Let's solve the first equation for [tex]\( y \)[/tex] in terms of [tex]\( x \)[/tex]:
[tex]\[ x + y = 7xy \][/tex]
[tex]\[ y = \frac{x}{7xy - 1} \][/tex]
However, it looks simpler to attempt solving this by substitution or another method since it results in a complicated expression.
### Step 3: Consider substitution and simultaneous solution
One approach to find the solution for such equations is to consider possible values for [tex]\( x \)[/tex] and [tex]\( y \)[/tex] that could simplify the terms.
### Step 4: Check possible simple solutions
Notice that [tex]\( x = 0 \)[/tex] and [tex]\( y = 0 \)[/tex] might simplify the equations dramatically:
- Substitute [tex]\( x = 0 \)[/tex] and [tex]\( y = 0 \)[/tex] in the first equation:
[tex]\[ 0 + 0 = 7 \times 0 \times 0 \][/tex]
[tex]\[ 0 = 0 \][/tex] which is true.
- Substitute [tex]\( x = 0 \)[/tex] and [tex]\( y = 0 \)[/tex] in the second equation:
[tex]\[ 2 \times 0 - 3 \times 0 + 0 \times 0 = 0 \][/tex]
[tex]\[ 0 = 0 \][/tex] which is also true.
Therefore, [tex]\((x, y) = (0, 0)\)[/tex] is one solution.
### Step 5: Find other potential solutions by solving equations simultaneously
Let's plug [tex]\( y = 1/4 \)[/tex] into the first equation to find another possible solution:
[tex]\[ x + \frac{1}{4} = 7x \left(\frac{1}{4}\right) \][/tex]
[tex]\[ x + \frac{1}{4} = \frac{7x}{4} \][/tex]
Multiplying through by 4 to clear the fraction:
[tex]\[ 4x + 1 = 7x \][/tex]
[tex]\[ 1 = 3x \][/tex]
[tex]\[ x = \frac{1}{3} \][/tex]
Check if [tex]\( x = \frac{1}{3} \)[/tex] and [tex]\( y = \frac{1}{4} \)[/tex] satisfy the second equation:
[tex]\[ 2 \times \frac{1}{3} - 3 \times \frac{1}{4} + \left(\frac{1}{3}\right)\left(\frac{1}{4}\right) = 0 \][/tex]
[tex]\[ \frac{2}{3} - \frac{3}{4} + \frac{1}{12} = 0 \][/tex]
Convert to a common denominator (12):
[tex]\[ \frac{8}{12} - \frac{9}{12} + \frac{1}{12} = 0 \][/tex]
[tex]\[ \frac{8 - 9 + 1}{12} = 0 \][/tex]
[tex]\[ \frac{0}{12} = 0 \][/tex]
This is also true, so [tex]\((x, y) = \left(\frac{1}{3}, \frac{1}{4}\right)\)[/tex] is another solution.
### Conclusion:
The solutions to the system of equations are:
[tex]\[ \boxed{(0, 0) \text{ and } \left(\frac{1}{3}, \frac{1}{4}\right)} \][/tex]
[tex]\[ \begin{cases} x + y = 7xy \\ 2x - 3y + xy = 0 \end{cases} \][/tex]
we need to find the values of [tex]\( x \)[/tex] and [tex]\( y \)[/tex] that satisfy both equations.
### Step 1: Rearrange and simplify the equations
First, let's work with the first equation:
[tex]\[ x + y = 7xy \][/tex]
We can rearrange this to express it in a different form:
[tex]\[ x + y - 7xy = 0 \][/tex]
Next, let's look at the second equation:
[tex]\[ 2x - 3y + xy = 0 \][/tex]
### Step 2: Solve one equation for one variable
Let's solve the first equation for [tex]\( y \)[/tex] in terms of [tex]\( x \)[/tex]:
[tex]\[ x + y = 7xy \][/tex]
[tex]\[ y = \frac{x}{7xy - 1} \][/tex]
However, it looks simpler to attempt solving this by substitution or another method since it results in a complicated expression.
### Step 3: Consider substitution and simultaneous solution
One approach to find the solution for such equations is to consider possible values for [tex]\( x \)[/tex] and [tex]\( y \)[/tex] that could simplify the terms.
### Step 4: Check possible simple solutions
Notice that [tex]\( x = 0 \)[/tex] and [tex]\( y = 0 \)[/tex] might simplify the equations dramatically:
- Substitute [tex]\( x = 0 \)[/tex] and [tex]\( y = 0 \)[/tex] in the first equation:
[tex]\[ 0 + 0 = 7 \times 0 \times 0 \][/tex]
[tex]\[ 0 = 0 \][/tex] which is true.
- Substitute [tex]\( x = 0 \)[/tex] and [tex]\( y = 0 \)[/tex] in the second equation:
[tex]\[ 2 \times 0 - 3 \times 0 + 0 \times 0 = 0 \][/tex]
[tex]\[ 0 = 0 \][/tex] which is also true.
Therefore, [tex]\((x, y) = (0, 0)\)[/tex] is one solution.
### Step 5: Find other potential solutions by solving equations simultaneously
Let's plug [tex]\( y = 1/4 \)[/tex] into the first equation to find another possible solution:
[tex]\[ x + \frac{1}{4} = 7x \left(\frac{1}{4}\right) \][/tex]
[tex]\[ x + \frac{1}{4} = \frac{7x}{4} \][/tex]
Multiplying through by 4 to clear the fraction:
[tex]\[ 4x + 1 = 7x \][/tex]
[tex]\[ 1 = 3x \][/tex]
[tex]\[ x = \frac{1}{3} \][/tex]
Check if [tex]\( x = \frac{1}{3} \)[/tex] and [tex]\( y = \frac{1}{4} \)[/tex] satisfy the second equation:
[tex]\[ 2 \times \frac{1}{3} - 3 \times \frac{1}{4} + \left(\frac{1}{3}\right)\left(\frac{1}{4}\right) = 0 \][/tex]
[tex]\[ \frac{2}{3} - \frac{3}{4} + \frac{1}{12} = 0 \][/tex]
Convert to a common denominator (12):
[tex]\[ \frac{8}{12} - \frac{9}{12} + \frac{1}{12} = 0 \][/tex]
[tex]\[ \frac{8 - 9 + 1}{12} = 0 \][/tex]
[tex]\[ \frac{0}{12} = 0 \][/tex]
This is also true, so [tex]\((x, y) = \left(\frac{1}{3}, \frac{1}{4}\right)\)[/tex] is another solution.
### Conclusion:
The solutions to the system of equations are:
[tex]\[ \boxed{(0, 0) \text{ and } \left(\frac{1}{3}, \frac{1}{4}\right)} \][/tex]
We appreciate your time. Please revisit us for more reliable answers to any questions you may have. Thanks for stopping by. We strive to provide the best answers for all your questions. See you again soon. We're dedicated to helping you find the answers you need at Westonci.ca. Don't hesitate to return for more.